Low concentration toxic metal mixture interactions: Effects on essential and non-essential metals in brain, liver, and kidneys of mice on sub-chronic exposure. (August 2015) - Cobbina, Samuel J.; Chen, Yao; Zhou, Zhaoxiang; Wu, Xueshan; Feng, Weiwei; Wang, Wei; Mao, Guanghua; Xu, Hai; Zhang, Zhen; Wu, Xiangyang; Yang, Liuqing
Highlights: Low dose metal mixtures interacted with toxic and essential metals. Interaction within metal mixtures were largely synergistic. Low dose exposures influenced homeostasis of toxic and essential metals. Essential metals in liver were influenced most by low dose metal mixtures. Elevation in toxic metals were linked to reductions in essential metals. Abstract: The deleterious effects of long term exposure to individual toxic metals in low doses are well documented. There is however, a paucity of information on interaction of low dose toxic metal mixtures with toxic and essential metals. This study reports on interactions between low dose mixtures of lead (Pb), mercury (Hg), arsenic (As) and cadmium (Cd) and toxic and essential metals. For 120 d, six groups of forty mice each were exposed to metal mixtures, however, the control group was given distilled water. Exposure to Pb + Cd increased brain Pb by 479% in 30 d, whiles Pb + Hg + As + Cd reduced liver Hg by 46.5%, but increased kidney As by 130% in 30 d. Brain Cu, increased by 221% on Pb + Hg + As + Cd exposure, however, liver Ca reduced by 36.1% on Pb + Hg exposure in 60-d. Interactions within metal mixtures were largely synergistic. Principal component analysis (PCA) showed that low dose metal exposures influenced greatly levels of Hg (in brain and liver) and As (brain). The influence exerted on essential metals was highest in liver (PC1) followed by kidney (PC2) and brain (PC3). Exposure to low dose metal mixtures affected homeostasis of toxic and essential metals in tissues of mice.